Solar Cell Prototype with TiO2 as an Electrode and Utilization of Dragon Fruit Peel as a Photosensitizer - Fayyaza Amalia Islami; Nurfi Misyka; Zulfa Firdausi Husna; Siti Yanuar Arofah; Ilma Khoirunissa (Jurnal Integrasi Sains dan Quran, 2023)
Energy is important part in human life. However, energy sources in Indonesia are still dominated by non-renewable energy sources. The depletion of non-renewable energy sources, there is a shift to use renewable energy sources, one of which is solar cells. Dye Sensitized Solar Cell (DSSC) is a device that can convert light energy into electrical energy. DSSC is a third-generation solar cell consisting of TiO2 semiconductors placed on a conductive glass substrate and immersed with dyestuffs. The dye as a sensitizer used comes from the skin of the red dragon fruit (Hylocereus costaricensis). DSSC is formed with a sandwich structure, there are five parts, namely ITO glass (Indium Tin Oxide) as a substrate, TiO2 as a semiconductor material, dye (red dragon fruit skin) as an electron donor, gel electrolyte as electron transfer and active carbon as a catalyst in the comparison. This study aims to prove that organic compounds can be used as photosensitizers to produce solar-powered electric current. Researchers use descriptive methods with a quantitative approach. The test methods carried out are voltage tests, electric current tests, fill factors, power, and efficiency. Based on the tests carried out, the results of the voltage test of 199.3 mV, the electric current test of 199.3 mV, the Fill Factor of 1.379%, and the efficiency of 1.948 x10-5%. This research successfully proved that DSSC with Dragon Fruit Skin as a photosensitizer can produce electrical current and voltage.